I have system of equation:

**k * G = P**

**k2(+/-N) * G(+/-N) = P**

variables:

G = 6

P = 36

k2 = 11

j2 = 3

what will be the formula for calculating k from k2, j2 and maybe P ?

1 | initial version |

I have system of equation:

**k * G = P**

**k2(+/-N) * G(+/-N) = P**

variables:

G = 6

P = 36

k2 = 11

j2 = 3

what will be the formula for calculating k from k2, j2 and maybe P ?

I have system of equation:

**k * G = P**

**k2(+/-N) * G(+/-N) = P**

variables:

G = 6

P = 36

k2 = 11

j2 = 3

what will be the formula for calculating k from k2, j2 and maybe P ?

I have system of equation:

**k * G = P**

**k2(+/-N) * G(+/-N) = P**

variables:

G = 6

P = 36

k2 = 11

j2 = 3

**what will be is the formula symbolic solution for calculating k from k2, j2 and maybe P ?**

I have system of equation:

**k * G = P**

**k2(+/-N) * G(+/-N) = P**

variables:

G = 6

P = 36

k2 = 11

j2 = 3

**what is the symbolic solution for calculating k from k2, j2 and maybe P ?**

I have system of equation:

**k * G = P**

**k2(+/-N) * G(+/-N) j2(+/-N) = P**

variables:

G = 6

P = 36

k2 = 11

j2 = 3

**what is the symbolic solution for calculating k from k2, j2 and maybe P ?**

I have system of equation:

**k * G = P**

**k2(+/-N) * j2(+/-N) = P**

variables:

G = ~~6~~6 (Constant !!!)

P = 36

k2 = 11

j2 = 3

**what is the symbolic solution for calculating k from k2, j2 and maybe P ?**

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.